Effect of the COVID-19 Pandemic on Consumers’ Impulse Buying: The Moderating Role of Moderate Thinking - Shuyang Wang (MDPI AG, 2021)
Based on event systems theory, this study examined the impact of the COVID-19 pandemic on consumers’ impulse buying, as well as the underlying mechanisms and boundary conditions from the perspective of individual consumers. Results of three experiments (N = 437) show that, first, the COVID-19 pandemic enhanced consumers’ impulse buying behavior. Second, two key elements, loss of control and anxiety, mediated the relationship between the COVID-19 pandemic and impulse buying; and third, moderate thinking (also known as Zhong-Yong thinking) moderated the relationship between the COVID-19 pandemic and impulse buying. The findings indicate that in consumers with low moderate thinking, the COVID-19 pandemic has had a stronger effect on impulse buying and has mediated more between the loss of control and anxiety. Conversely, in consumers with high moderate thinking, COVID-19 has had a weaker effect on impulse buying and has mediated less between loss of control and anxiety. This study extends the application of event systems theory and enriches the literature on how the COVID-19 pandemic affects consumer behavior. Furthermore, it provides strategic recommendations for government and consumer responses to COVID-19 pandemic shocks.